Synthesis of Heteroaromatic Derivatives with Nitrogen Atoms: Tripyrrolyl Pyrimidine and Tripyrrolyl[1,3,5]triazine - Lee, D.H.; Lee, S.G.; Jung, D.I.; Hahn, J.T. (Asian Journal of Chemistry, 2012)
As a part of a research program related to the synthetic study of pharmacologically and photoconductively interesting pyrrole derivatives, we have synthesized 1-arylpyrroles (3a-e), 9-arylcarbazoles (4a-e), aminophenylpyrroles (6a,b), dipyrrolylbenzenes (7a-c), 2,4,6-tri-pyrrol-1-yl-pyrimidine (8) and 2,4,6-tri-pyrrol-1-yl[1,3,5]triazine (9). We proposed a plausible mechanism for the formation of 9-arylcarbazole.